Factors of Primary Postpartum Hemorrhage among Women Delivered at Yirgalem General Hospital Southern, Ethiopia: A case control study - Gebretsadik, Achamyelesh; Melaku, Nebiyu (Journal of Maternal and Child Health, 2021)
Background: Primary postpartum hemorrhage continues to be the top leading cause of maternal mortality and morbidity all over the world, contributing about one third of all maternal mortality. Despite its public health importance of this problem, little is known about factors that contribute to primary postpartum hemorrhage especially in Ethiopia. The aim of this study was to assess the risk factors of primary postpartum hemorrhage. Subjects and Method: Hospital based unmatched case control study design was used. The study was conducted in July 2019, among delivered women at Yirgalem general hospital from January 1, 2014 to December 30, 2018; to all cases of primary postpartum hemorrhage (n= 218) and 436 controls selected by using simple random sampling techniques. Women with primary postpartum hemorrhage were cases and women who had not diagnosed for primary postpartum hemorrhage were controls. Descriptive statistics and logistic regression analysis were made. Statistical association was measured by AOR and its 95% CI. Results: Incidence of primary postpartum hemorrhage was 221 in 8,506 live births (2.6%) in the study period. Primiparas (AOR= 0.37 ;95% CI= 0.23 to 0.6; p= 0.001), grand multiparas (AOR= 5.80; 95% CI= 2.90 to 11.6; p <0.000) and rural maternal address (AOR= 1.90; 95% CI= 1.20 to 3.00; p= 0.008) were factors that have a statistically significant association with primary postpartum hemorrhage. Conclusion: Parity and rural residence were associated factors. Therefore, the government and other responsible stakeholders should give attention to women with grand multiparas and those women residing in rural area. Immediate identification of risk factors and management might reduce largely the occurrence of primary PPH and related maternal deaths.